Using the Lanchester sport combat theory model to analyze the competitive entry strategy of the cross-border e-commerce market in southeast Asia – for example as cross-border e-commerce in Taiwan, China - Huang, Wenya; Irina, Mukambaeva; Huang, Dalin; Dzhanuzakov, Kanat; Leu, Jai-Houng (Edelweiss Applied Science and Technology, 2025)
The World Trade Organization (WTO) defines cross-border e-commerce as "the cross-border transaction of goods and services by electronic means" [1]. When entering the target market, enterprises need to clarify their market positioning, systematically analyze the overall competitive environment, evaluate their comprehensive competitiveness relative to competitors, and use market share as the core indicator to differentiate their advantages. Additionally, enterprises can utilize multi-attribute decision-making (MADM) methods to enhance the scientific and effective decision-making process. This study aims to provide feasible suggestions on competitive positioning and market entry strategies for Taiwanese cross-border e-commerce enterprises seeking to expand into the ASEAN market, thereby supporting their sustainable development in the regional market. Taiwan’s competitiveness in the Southeast Asian e-commerce market is approximately 3 to 10 times smaller than that of major competitors, and according to Lanchester’s law of range, this market is in the range of 0.20. The total size of the e-commerce market across the six ASEAN countries reached 7 billion US dollars, accounting for 0.7% of the global market. Taiwan, China strives for the e-commerce market potential of the six ASEAN countries = 3.47/0.7 = 4.95 7, and Taiwan, China strives for the e-commerce market potential of the six ASEAN countries = 3.47/0.7 = 4.95 7, and it is estimated that the potential market share of Taiwan’s e-commerce in ASEAN is 4.95 times the current level. Taiwan’s strategic focus is on Vietnam, Thailand, and the Philippines, among which Vietnam presents the biggest opportunity. Taiwan, China, strives for Vietnam’s global e-commerce market potential, calculated as 3.47/0.08=43.37. Taiwan, China’s global e-commerce market potential is 3.47/0.08=43.37, and it is estimated that the potential market share of Taiwan’s e-commerce in Vietnam is 43.37 times the current level.